Pengaruh Edukasi Teknik Menyusui Yang Benar Pada Ibu Nifas Primipara Terhadap Keterampilan Dalam Menyusui Di Rsud Toto Kabila - Hilamuhu, Fendrawaty; Sondakh, Levana; Marif, Susanti; Djunaid, Ulfiana (Madu : Jurnal Kesehatan, 2023)
Breastfeeding is a natural process, but often mothers do not succeed in breastfeeding properly, therefore mothers need help so that the breastfeeding process can be successful. Objective: to determine the effect of correct breastfeeding technique education in primiparous postpartum mothers on breastfeeding skills at Toto Kabila Hospital. Methods: This study used a pre-experimental one group pre and posttest design. Samples were taken using positive sampling technique of 53 respondents. Results: The results showed that the posttest breastfeeding technique showed a mean value of 94.45 with a standard deviation of 4.685, a minimum value of 82 and a maximum value of 100.Where is greater than the pretest value, the mean value is 53.43 with a standard deviation of 8.664, a minimum value of 41 and The maximum value is 76. Based on the calculation results, the Z value obtained is -6,366 with a p value (Asymp. Sig 2 tailed) of 0,000, which is less than the critical research limit of 0.05 so that the hyphesis decision Ha is accepted, which means that there is a significant difference between the pretest groups. and posttest. Where there is an effect of correct breastfeeding technique education in primiparous postpartum mothers on breastfeeding skills at Toto Kabila Hospital.